HUBUNGAN PSYCHOLOGICAL CAPITAL DENGAN MASALAH PSIKOSOSIAL PADA MAHASISWA - SEBUAH STUDI LITERATUR - Fitria, Dian (Jurnal Kesehatan Holistic, 2017)
Anxiety and stress disorders are a problem experienced by many people in all ages including college students. Among the many research departments mentioned that health majors students have higher levels of stress and anxiety than other majors. The most dominant stressors are academic stressors. The research shows the psychosocial problem faced by the health student is high enough that is 82% stress, 60% anxetas, and 51% depression. This study aims to determine the relationship between stress, anxiety with psychological capital (hope, optimism, self efficacy, & resilience) in the students. The literature search finds six articles that are compatible with the theme. The six researches are descriptive quantitative research and pre and post experiment. All literature analyzes conducted reveal consistent results that there are psychosocial problems in the students and have relationship with psychological capital (hope, optimism, self efficacy, & resilience) owned. Psychosocial problems that have the highest value of stress and anxiety. The results show the higher the psychological capital possessed the better the ability of students in facing anxiety and stress.